Sf. Ierarh Petru Movilă și instituțiile de învățământ - But-Căpușan, Dacian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The study highlights the activity of Peter Mogila, first abbot of the Pecerska Lavra, then Metropolitan of Kyiv as founder, organizer and supporter of educational institutions in today’s Ukraine. Peter Mogila introduced Western humanism, the study of the Latin language and interest in scientific research into the space of the Eastern Slavs. To him is due the first truly academic institution among the Orthodox Slavs and throughout Orthodoxy. It had a syllabus identical to that of higher schools in the West (very rich, emphasizing the humanities), a thoroughly trained teaching staff and a rich library. In 1833, on the foundation of the Theological Academy, the University of Kiev was formed. The Metropolitan of Kiev also established other smaller schools, all financed by the money from the Pecerska Lavra, with the aim of preparing the students who will end up at the Movilean Academy. He also established a second Academy in Vinnytsa and a college in Kremenits. The schools organized according to the model of the Kiev Academy are also listed: in Iaşi, Putna and Moscow, as well as the ecclesiastical personalities who studied at the Kiev Academy: hierarchs (some passed among the saints), professors of Theology, scholars, people of culture and the Romanian graduates.